The Influence of Work Culture and Proactive Personality on Job Satisfaction and its Impact on Job Performance - Budi; Chatrine Gouwtama; Sugiyanto (Komunitas Dosen Indonesia, 2024)
The objective of this study is to examine the interplay between work culture, proactive personality, job satisfaction, and job performance among employees, with a focus on investigating whether job satisfaction mediates the relationship between work culture and proactive personality with job performance. The scope of the research encompasses analyzing these factors within the context of organizational dynamics and employee behavior, aiming to provide insights for organizations to optimize their work environments and enhance employee performance. This study delves into the intricate relationship between work culture, proactive personality traits, job satisfaction, and employee performance. By exploring whether job satisfaction mediates the link between work culture, proactive personality, and performance, the research seeks to enhance working conditions and employee effectiveness. Employing Partial Least Square (PLS) analysis within Structural Equation Modeling (SEM), the study examines these relationships, revealing robust levels of work culture (mean = 4.17), proactive personality (mean = 4.07), job satisfaction (mean = 3.84), and performance (mean = 4.05), indicative of a positive organizational climate. Regression analysis underscores the significant impact of work culture and proactive personality on job satisfaction and performance, highlighting the importance of nurturing these attributes for heightened employee satisfaction and productivity. Ultimately, the study emphasizes the profound influence of work culture and proactive traits on job satisfaction and performance, advocating for the cultivation of positive work environments and proactive characteristics. Moreover, the identification of job satisfaction as a mediator offers valuable insights for organizational strategies aimed at improving employee satisfaction and productivity.